The role of tributary mixing in chemical variations at a karst spring, Milandre, Switzerland - Perrin, J.; Jeannin, Pierre-Yves; Cornaton, Fabien (My University, 2007)
Solute concentration variations during flood events were investigated in a karst aquifer of the Swiss Jura. Observations were made at the spring, and at the three main subterraneous tributaries feeding the spring. A simple transient flow and transport numerical model was able to reproduce chemographs and hydrographs observed at the spring, as a result of a mixing of the concentration and discharge of the respective tributaries. Sensitivity analysis carried out with the model showed that it is possible to produce chemical variations at the spring even if all tributaries have constant (but different for each of them) solute concentrations. This process is called tributary mixing. The good match between observed and modelled curves indicate that, in the phreatic zone, tributary mixing is probably an important process that shapes spring chemographs. Chemical reactions and other mixing components (e.g. from low permeability volumes) have a limited influence.
Dissolution-related (calcium, bicarbonate, specific conductance) and pollution-related parameters (nitrate, chloride, potassium) displayed slightly different behaviours: during moderate flood events, the former showed limited variations compared to the latter. During large flood events, both presented chemographs with significant changes. No significant event water participates in moderate flood events and tributary mixing will be the major process shaping chemographs. Variations are greater for parameters with higher spatial variability (e.g. pollution-related). Whereas for large flood events, the contribution of event water becomes significant and influences the chemographs of all the parameters. As a result, spring water vulnerability to an accidental pollution is low during moderate flood events and under base flow conditions. It strongly increases during large flood events, because event water contributes to the spring discharge.